Trans Issues in Liz Lochhead’s “Not Changed” - Kaličanin, Milena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper is divided into four sections. In the first section entitled “Introducing and Defining Trans (Issues)”, the basic terms of transgender, transvestite, and transsexual are defined by relying on Stryker’s Transgender History (2008). The second part of the paper, “Trans Studies: In-Between Feminist and Queer Theory?”, places transgender studies into an academic context by referring to the theoretical framework provided by trans theorists Stryker, Stone, and Ranck who unanimously claim that transgender studies should have a place of its own within the academia and that trans theory should solely be written by transsexuals. These ideas are applied in the interpretation of Lochhead’s story “Not Changed” in the third segment of the paper. The critical insights of Butler (Gender Trouble, 1990; Undoing Gender, 2004) are found to be most helpful in the interpretation of Lochhead’s story about Michael who has willingly undergone Hormone Replacement Therapy to become transsexual Michele. Finally, in the concluding remarks, Lochhead’s story is viewed as a trans woman manifesto, urging both non-transsexual and transsexual persons to embrace new beginnings in their relationship.
Keywords: gender dysphoria; trans-misoginy; transsexual; transvestite; transgender